Entrepreneurship education and green entrepreneurial intention: mediating role of green economy attitudes - Efni Cerya; Idris Idris; Joan Marta; Nuri Latifannisa; Nur Alfiana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Many consider entrepreneurship education (EE) a significant factor in deciding a person's inclination towards green entrepreneurship (GEI). Yet, few have examined the possible mediating effect of green economy attitude (GEA) in how participants' entrepreneurship education influences their intention to initiate environment-oriented business, especially in a developing country scenario. This paper examines the direct and indirect links between entrepreneurship education, green economy attitude, and green entrepreneurship intention among Indonesian university students. A quant survey cross-sectional design was employed to collect data from 196 students who had attended entrepreneurship classes. A structured Likert scale questionnaire was used to collect the data which were then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the support of SmartPLS 4 software. The measurement model showed good results in terms of convergent validity (AVE > 0.50), composite reliability (CR > 0.70), and discriminant validity (HTMT < 0.85). The structural model unveiled the fact that entrepreneurship education has a great impact on green economy attitude (β = 0.643, p < 0.001) and green entrepreneurship intention (β = 0.494, p < 0.001). Green economy attitude, on the other hand, also has a significant positive impact on green entrepreneurship intention (β = 0.472, p < 0.001). Further mediation analysis showed that green economy attitude acts as a partial mediator of the entrepreneurship education-green entrepreneurship intention link. The results of this study provide empirical support for green entrepreneurship literature in the context of the Indonesian higher education sector.